2020
DOI: 10.1038/s41598-020-58803-z
|View full text |Cite
|
Sign up to set email alerts
|

Trazodone Loaded Lipid Core Poly (ε-caprolactone) Nanocapsules: Development, Characterization and in Vivo Antidepressant Effect Evaluation

Abstract: trazodone Loaded Lipid core poly (ε-caprolactone) nanocapsules: Development, characterization and in Vivo Antidepressant Effect evaluation nahla elhesaisy 1 & Shady Swidan 1,2* Trazodone hydrochloride (TRH) is a lipophilic drug which is used effectively as an antidepressant. Its poor solubility and short half-life represent an obstacle for its successful use. Nanocapsules with biodegradable polymeric shell are successful drug delivery systems for controlling the release of drugs. to enhance the entrapment of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The results in Table 2 also revealed that the %EE values for LNCs (F4, F5, and F6) were higher than PNCs (F1, F2, and F3) and this could be related to the inclusion of lipids in the core of nanocapsules structure where highly lipophilic drugs could be concentrated in (El-Hesaisy & Swidan, 2020 ). As well as they donate thick shell for nanocapsules; allow higher amount of drug entrapment as well as slower release (Radwan et al., 2020 ).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The results in Table 2 also revealed that the %EE values for LNCs (F4, F5, and F6) were higher than PNCs (F1, F2, and F3) and this could be related to the inclusion of lipids in the core of nanocapsules structure where highly lipophilic drugs could be concentrated in (El-Hesaisy & Swidan, 2020 ). As well as they donate thick shell for nanocapsules; allow higher amount of drug entrapment as well as slower release (Radwan et al., 2020 ).…”
Section: Resultsmentioning
confidence: 96%
“…The negative zeta potential of LNCs (–25.23 ± 3.72 to −33.22 ± 2.1) may be attributed to the amphiphilic surfactant soy phosphatidylcholine as well as presence of oleic acid in the oil core which has strong negative charge (Xia et al., 2017 ; El-Hesaisy & Swidan, 2020 ). Consequently, by increasing lipid content with respect to MN, zeta potential increased ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have reported variation in the entrapment efficiency of active ingredients in carriers using various lipids or oils. This is because drugs demonstrate a variable solubility in these lipids and oils [37,38].…”
Section: Drug Loading and Entrapment Efficiencymentioning
confidence: 99%